2011
DOI: 10.1016/s0027-9684(15)30448-x
|View full text |Cite
|
Sign up to set email alerts
|

On the Frontline: Pediatric Obesity in the Emergency Department

Abstract: Obesity among children is rising at an alarming rate. This study examines pediatric emergency department visits for children aged 2 to 17 years to determine the prevalence of normal, overweight, and obesity as well as to characterize discharge diagnosis and level of service among the different groups. The electronic emergency department medical record and billing service data were used in the review process. Body mass index (BMI) and percentiles were calculated using the Centers for Disease Control formulas wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…This study had both strengths and weaknesses. The PED can be an acceptable setting to screen health behaviors related to obesity risk and for brief interventions, particularly because it provides health care to high-risk populations, such as low-income, minority families [6,7,8,9]. Additionally, this study utilized the PALS diet and activity screener, which was acceptable to both children and parents, with testing of reliability and validity using multiple statistical techniques and criteria [34,97].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study had both strengths and weaknesses. The PED can be an acceptable setting to screen health behaviors related to obesity risk and for brief interventions, particularly because it provides health care to high-risk populations, such as low-income, minority families [6,7,8,9]. Additionally, this study utilized the PALS diet and activity screener, which was acceptable to both children and parents, with testing of reliability and validity using multiple statistical techniques and criteria [34,97].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity prevention requires a multi-sector approach [3], including screening, brief interventions and referrals between clinical and community sectors [4]. As the pediatric emergency department (PED) is utilized for non-urgent care [5], it should be part of this multi-sector approach [6,7,8,9] to reach low-income children who often have unhealthy dietary behaviors and lack access to primary care [6]. Brief obesity interventions have been successfully accomplished in the PED [7].…”
Section: Introductionmentioning
confidence: 99%
“…(Stettler et al, 2007) The latter implies that there may be some value in using weight-for-age > 95th percentile as a clinical screening tool for obesity in the emergency department. An earlier study out of the United States identified that approximately 30% of children who present to an urban emergency department are obese, (Prendergast et al, 2011) and the reported prevalence in this study's population was approximately 16%. Thus, the emergency setting may be a significant untapped resource in identifying childhood obesity.…”
Section: Discussionmentioning
confidence: 58%
“…That is, we may have had a higher percentage of children that were shorter and obese with a weightfor-age percentile that did not meet the obesity cut-off. The latter may be relevant in our study since compared to the general population, there is a greater frequency of childhood obesity amongst those who present to emergency departments, (Prendergast et al, 2011) and we may have had on average shorter children given the relatively higher proportion of Southeast Asian participants. Thus, weight-for-age > 95th percentile may have falsely labelled some shorter children as non-obese, thereby compromising the sensitivity of this definition for obesity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation